TINGKAT KENYAMANAN PENGGUNA KNOWLEDGE MANAGEMENT SYSTEM DALAM MENDUKUNG BUDAYA BERBAGI PENGETAHUAN MENGGUNAKAN METODE COLLES - Esron Rikardo Nainggolan (Universitas Bina Sarana Informatika, 2016)
The application of current knowledge management system is needed in every aspect, especially on education. Therefore, the ability of each college are manage the knowledges into its own power for the institution to be able compete in improving education in Indonesia. At the School of Theology Intercultural Knowledge Management System has been implemented by using a Learning Management System (LMS) Moodle. Implementatio of knowledge management system based on time and place for the sharing limited knowledge of theology. The purpose of this study is determine how much the convenience Management of knowledge users sharing culture system in favor of the theology between teachers and students in the School of Theology Lintas Budaya Jakarta. The results showed